2014
DOI: 10.1007/s11356-014-2851-6
|View full text |Cite
|
Sign up to set email alerts
|

NAPL migration and ecotoxicity of conventional and renewable fuels in accidental spill scenarios

Abstract: Fuels derived from non-petroleum renewable resources have raised interest due to their potential in replacing petroleum-based fuels, but information on their fate and effects in the terrestrial and aquatic environments in accidental spill scenario is limited. In this study, migration of four fuels (conventional diesel, conventional gasoline, renewable diesel NExBTL, and ethanol-blended gasoline RE85 containing maximum 85% ethanol) as non-aqueous phase liquids (NAPL) in soil was demonstrated in a laboratory-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Halmemies et al (2003) measured the short-term (2 h) retention capacities in laboratory-scale column experiments and found that sandy till can retain 1.5–2 times and peat 3.5 times more fuel than gravely sand (measured as volume percent of retained fuel from soil volume). In the same study, the moisture content had minor effects on retention, but instead a significant effect on fuel migration velocity, the migration being faster in dry than in wet sand, as noticed also by Malk et al (2014). When comparing migration velocities of different fuels, gasoline with low viscosity has been observed to migrate seven to nine times faster than diesel in sand (Malk et al 2014) and three times faster in sandy till or peat (Halmemies et al 2003).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Halmemies et al (2003) measured the short-term (2 h) retention capacities in laboratory-scale column experiments and found that sandy till can retain 1.5–2 times and peat 3.5 times more fuel than gravely sand (measured as volume percent of retained fuel from soil volume). In the same study, the moisture content had minor effects on retention, but instead a significant effect on fuel migration velocity, the migration being faster in dry than in wet sand, as noticed also by Malk et al (2014). When comparing migration velocities of different fuels, gasoline with low viscosity has been observed to migrate seven to nine times faster than diesel in sand (Malk et al 2014) and three times faster in sandy till or peat (Halmemies et al 2003).…”
Section: Discussionsupporting
confidence: 73%
“…In the same study, the moisture content had minor effects on retention, but instead a significant effect on fuel migration velocity, the migration being faster in dry than in wet sand, as noticed also by Malk et al (2014). When comparing migration velocities of different fuels, gasoline with low viscosity has been observed to migrate seven to nine times faster than diesel in sand (Malk et al 2014) and three times faster in sandy till or peat (Halmemies et al 2003). Those results are consistent with observations presented here, although we performed the spill using a mixture of gasoline and diesel.…”
Section: Discussionsupporting
confidence: 73%
“…Figure 1 shows the main guidelines for activity pollution control in contaminated sites. NAPL constituents may partition or move from one phase to another depending on environmental conditions: the tendency for a contaminant to associate to one phase or another may be examined by empirical partition coefficients dependent on the properties of the pollutant and the subsurface materials [4][5][6]. NAPLs can be divided into two groups according to their density: denser than water, dense non-aqueous phase liquids (DNAPLs) and less dense than water, light nonaqueous phase liquids (LNAPLs).…”
Section: Introductionmentioning
confidence: 99%
“…Soil and groundwater contamination resulting from the release of petroleum hydrocarbons can pose significant risks and carcinogenic effects into the human health. Following release near the ground surface, organic hydrocarbons start a complex migration and distribute as a non-aqueous phase liquid (NAPL) in the subsurface system (Gan et al 2009;Malk et al 2014;Al-Raoush 2014;Acosta-gonzález et al 2015). Anaerobic biodegradation is the most dominant process in the organiccontaminated soil and groundwater due to depletion of dissolved oxygen by aerobic respiration processes (Anderson and Lovley 1997;Perelo 2010).…”
Section: Introductionmentioning
confidence: 99%